Pengaruh Green Awareness, Brand Image, dan Brand Trust Terhadap Keputusan Pembelian Produk The Body Shop di Kota Surakarta - Ababil, Adeline; Walyoto, Sri (Journal of Economics and Business Research (JUEBIR), 2024)
This quantitative research aims to determine the influence of green awareness, brand image, and trust on purchasing decisions. The sample used in this research was 100 respondents from The Body Shop consumers in Surakarta City. The data collection method was a questionnaire distributed to The Body Shop Surakarta City consumers. The sampling technique used is non-probability sampling with a purposive sampling approach where the researcher selects samples using certain and subjective criteria. Data analysis in this research uses multiple linear regression analysis by looking at the F statistical value and the T statistic. This research shows that the green awareness variable has a positive and significant influence on purchasing decisions. Meanwhile, the brand image variable has a negative and insignificant influence on purchasing decisions, and the brand trust variable has a positive and significant impact on purchasing decisions. Simultaneously or together, green awareness, brand image, and trust influence purchasing decisions. It is hoped that future researchers will use other variables or factors that can influence purchasing decisions.